Social Media in Southeast Italy Crafting Ideals - Nicolescu, Razvan (Why We Post, 2016)
Why is social media in southeast Italy so predictable when it is used by such a range of different people? This book describes the impact of social media on the population of a town in the southern region of Puglia, Italy. Razvan Nicolescu spent 15 months living among the town's residents, exploring what it means to be an individual on social media. Why do people from this region conform on platforms that are designed for personal expression?